2012
DOI: 10.1089/neu.2011.1811
|View full text |Cite
|
Sign up to set email alerts
|

Does an Early Onset and Continuous Chain of Rehabilitation Improve the Long-Term Functional Outcome of Patients with Severe Traumatic Brain Injury?

Abstract: There are currently no international guidelines regarding treatment in the early rehabilitation phase for persons with severe traumatic brain injury (TBI), and only a few studies have investigated the effect of integrating rehabilitation into acute TBI care. The aim of the study was to evaluate whether a continuous chain of rehabilitation that begins with the acute phase could improve the functional outcome of severe TBI patients, compared to a broken chain of rehabilitation that starts in the sub-acute phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
136
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 31 publications
6
136
2
3
Order By: Relevance
“…This is further supported by a reported average of five PTCs within different domains. Former studies have indicated that moderate and severe TBI patients often deal with various problems, and that rehabilitation physicians are important care providers in long-term aftercare for these patients [16,19]. We observed a relatively low follow-up rate with rehabilitation physicians.…”
Section: Discussionmentioning
confidence: 61%
“…This is further supported by a reported average of five PTCs within different domains. Former studies have indicated that moderate and severe TBI patients often deal with various problems, and that rehabilitation physicians are important care providers in long-term aftercare for these patients [16,19]. We observed a relatively low follow-up rate with rehabilitation physicians.…”
Section: Discussionmentioning
confidence: 61%
“…5,6,[44][45][46] Moreover, intensive rehabilitative therapy, which is presently the best available intervention for TBI patients, 19 is optimally effective when initiated early after the onset of injury. [47][48][49][50] In this study the VNS-paired intervention was initiated between 3 and 4 weeks post-injury, and it endured for 5 weeks. Therefore, the lower stimulation requirements and long therapeutic window demonstrate that paired VNS therapy is a promising candidate for patients who are suffering the longterm effects of brain injury.…”
mentioning
confidence: 99%
“…Initial treatment of STBI at a level 1 trauma center may be associated with a greater return of functional independence [37]. Continuous early rehabilitation interventions beginning during acute care and spanning IR and outpatient rehabilitation have been shown to improve outcomes after TBI [38][39][40][41]. Also, an investigation of veterans having nonpenetrating moderate TBI to STBI found that those with a latency of less than 48 d in trauma acute care prior to transfer to postacute IR were 2.4 times more likely to be productive in terms of ability to return to work at 1 yr [42].…”
Section: Discussionmentioning
confidence: 99%